Glucose‐Sensitive Hydrogel Optical Fibers Functionalized with Phenylboronic Acid. Issue 15 (13th February 2017) - Yetisen, Ali K.; Jiang, Nan; Fallahi, Afsoon; Montelongo, Yunuen; Ruiz‐Esparza, Guillermo U.; Tamayol, Ali; Zhang, Yu Shrike; Mahmood, Iram; Yang, Su‐A; Kim, Ki Su; Butt, Haider; Khademhosseini, Ali; et al.
Abstract : Hydrogel optical fibers are utilized for continuous glucose sensing in real time. The hydrogel fibers consist of poly(acrylamide‐ co ‐poly(ethylene glycol) diacrylate) cores functionalized with phenylboronic acid. The complexation of the phenylboronic acid and cis ‐diol groups of glucose enables reversible changes of the hydrogel fiber diameter. The analyses of light propagation loss allow for quantitative glucose measurements within the physiological range.